2021
DOI: 10.1088/1755-1315/892/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Policies and strategies for reducing food loss and waste in Indonesia

Abstract: Food loss and waste (FLW) have become one of the targets for Sustainable Development Goals (SDGs), which was agreed to achieve in 2030. This paper aims to provide policy recommendations and strategies to reduce FLW to achieve sustainable food and nutrition security in Indonesia. This paper used secondary data from FAO, BAPPENAS, and various references. Data were analyzed using descriptive analysis. FAO shows that one-third of the food available for human consumption at the global level is lost or wasted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Reducing food loss and waste, apart from being an ethical priority [98], may enhance food security through improving nutritional status and health in an environmentally sustainable manner [99], and reducing greenhouse gas emissions, a well-known driver of climate change [93,100]. Utilizing, in this direction, cutting edge technology across the food supply chain (including advancements in artificial intelligence, nanotechnology, robotics and automation [101]) may significantly reduce food loss [102].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing food loss and waste, apart from being an ethical priority [98], may enhance food security through improving nutritional status and health in an environmentally sustainable manner [99], and reducing greenhouse gas emissions, a well-known driver of climate change [93,100]. Utilizing, in this direction, cutting edge technology across the food supply chain (including advancements in artificial intelligence, nanotechnology, robotics and automation [101]) may significantly reduce food loss [102].…”
Section: Discussionmentioning
confidence: 99%
“…H. P. Saliem et al [12] have written a paper which clearly state that policy on food waste reduction is essential. However, the research needs provide a detailed list of the regulations that Indonesia has in place regarding food waste and their strengths and weaknesses.…”
Section: Social Impactsmentioning
confidence: 99%
“…However, another study found that harvesting time does not significantly affect food loss; instead, some factors that significantly affect food loss were field area, farmers' behavior, variety of paddy, and threshing tools [25]. Technology's importance in reducing food loss, particularly for chili and rice, has been reported [18]. Furthermore, in the case of consumer FLW, some efforts will be required to change the behavior of consumers, including intensive and massive education, socialization, and communication among stakeholders [18].…”
Section: 2mentioning
confidence: 99%
“…Technology's importance in reducing food loss, particularly for chili and rice, has been reported [18]. Furthermore, in the case of consumer FLW, some efforts will be required to change the behavior of consumers, including intensive and massive education, socialization, and communication among stakeholders [18]. 1, it can be calculated the average field area is 4,557 m 2 or 0,456 hectare, while the average yield is 1,325 kg per harvesting season or equal to 2,905.70 kg/hectare.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation